الأخطاء الصفية في تعليم اللغة العربية وتعلمها بالجامعة الإسلامية العالمية في ماليزيا استراتيجيات التصحيح = Classroom errors in teaching / learning Arabic language at the International Islamic University, Malaysia : strategies of correction - شمس الدين محمد نور (Jami'at al-Yarmuk, 2000)
Abstract in English and Arabic.